Development of a resilience focused psychoeducation program for families in a disaster prone community - Botor, Nephtaly Joel B. (College of Education, University of the Philippines Diliman, 2019)
This study aimed to develop a manualized eight-week Family Psychoeducation Program (FPP) for families (represented by mother and an adolescent child) in a disaster-prone community.